The Effect Of Marketing Communications Strategy And Promotion On Customer Loyalty With Customer Satisfaction As A Moderating Variable In Pt. Bank Rakyat Indonesia Tbk Especially In Work Units Kcp Diski Year 2019 - Purnomo, Dedi; Yusuf Ronny Edward; Syaifuddin; Sofiyan (International Journal of Science, Technology & Management, 2022)
The research was conducted with the aim of knowing the effect of marketing and promotional communication strategies on customer loyalty with customer satisfaction as the moderating variable. The study used primary data sourced from research questionnaires. The population in this study are customers at PT.Bank Rakyat Indonesia.Tbk, especially the KCP Diski work unit, amounting to 14,021 people. Then the sample used in the study was 100 respondents with saturated sampling technique. The data analysis method used Moderated Regression Analysis (MRA). The results showed that the Marketing Communication Strategy had a positive and significant effect on Customer Loyalty using BRI bank products. Promotion has a positive and significant impact on customer loyalty using BRI bank products. Customer satisfaction is not able to be a moderating variable of Marketing Communication Strategy on Customer Loyalty using BRI bank products. Customer satisfaction is not able to be a moderating variable of the level of promotion of customer loyalty using BRI bank products. Thus, the customer satisfaction variable cannot be an independent variable or an intervening variable.